Uniting individual and collective concerns through design: Priming across the senses. (March 2017) - Cash, Philip; Holm-Hansen, Christopher; Borum Olsen, Sebastian; Christensen, Mette Louise; Thi Trinh, Yen Mai
Abstract : This paper contributes to design for behaviour change by testing the potential of priming via everyday products as a means of influencing users and dissolving conflicting individual and collective concerns. Self-construal is introduced as a core explanatory concept with respect to behaviours that unite individual and collective concerns. Two studies are reported. In the first, abstract representations of the target behaviour are elicited and incorporated into subconscious priming stimuli for each of the major senses: sight, hearing, touch, and smell. These primes are then evaluated in a controlled experiment. From these studies implications for both researchers and practitioners are identified. In particular, priming showed a significant effect across all senses. Highlights: An experimental study distilling and implementing a behavioural design intervention. Demonstration of priming through everyday artefacts. Compares interventions targeting different senses: vision, hearing, smell, and touch. Elaborates self-construal as a means for dissolving individual and collective concerns. Key learnings for behaviour change through design are identified.